2016
DOI: 10.3897/bdj.4.e8051
|View full text |Cite
|
Sign up to set email alerts
|

The cicadas (Hemiptera: Cicadidae) of India, Bangladesh, Bhutan, Myanmar, Nepal and Sri Lanka: an annotated provisional catalogue, regional checklist and bibliography

Abstract: BackgroundThe cicadas of the Indian subcontinent, like many other insects in the region, have remained understudied since the early part of the 20th Century, and await modern taxonomic, systematic and phylogenetic treatment. This paper presents an updated systematic catalogue of cicadas (Hemiptera: Cicadidae) from India, Bangladesh, Bhutan, Myanmar, Nepal and Sri Lanka, the first in over a century.New informationThis paper treats 281 species, including: India and Bangladesh (189 species), Bhutan (19 species), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 1,086 publications
(9 citation statements)
references
References 80 publications
0
9
0
Order By: Relevance
“…Moreover, we found that relatively continuous sounds (>8 sec, generally insects) affected the ability of index models to predict vocal diversity. In this sense, the acoustic environment of the Western Ghats makes the use of acoustic indices challenging-particularly, the high density of animals that produce extended sounds covering a broad spectrum of frequencies (e.g., cicadas, (Diwakar and Balakrishnan, 2007;Price et al, 2016). However, the relationship between model residuals and continuous biological sounds was weak (confidence intervals near zero-Figure 6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we found that relatively continuous sounds (>8 sec, generally insects) affected the ability of index models to predict vocal diversity. In this sense, the acoustic environment of the Western Ghats makes the use of acoustic indices challenging-particularly, the high density of animals that produce extended sounds covering a broad spectrum of frequencies (e.g., cicadas, (Diwakar and Balakrishnan, 2007;Price et al, 2016). However, the relationship between model residuals and continuous biological sounds was weak (confidence intervals near zero-Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…However, properties of the acoustic environment could render the use of acoustic indices for analysis of recordings challenging. For example, there are high densities of insects which produce extended, constant, and broadband vocalizations (Diwakar and Balakrishnan, 2007;Price et al, 2016). This may confound a high diversity of bird song, which is characterized by an intrinsic variability of intensities (Pieretti et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Distribution. The genus in its new concept is found over much of Southeastern Asia including Borneo, Burma, Cambodia, China, Himalayas, India, Indonesia, Korea, Nepal, Philippine Republic, Thailand, and Vietnam (Metcalf 1963;Sanborn 2013;2015;Price et al 2016). It has yet to be recorded from Laos (Lee 2014…”
Section: Systematicsmentioning
confidence: 99%
“…The genus Rustia currently contains two species known to have distributional ranges in the Indian subcontinent, Himalayas, and Southeast Asia (Metcalf 1963;Duffels and van der Laan 1985;Sanborn 2013;2015;Price et al 2016). We add two new species from the Western Ghats, India to this group along with the reassignment of four species from Gudaba which we propose to be a junior synonym of Rustia.…”
Section: Introductionmentioning
confidence: 98%
“…Distant (1913) describes the distributional range of S. m. mirabilis as Indo-China; however, there exists no record of its occurrence in India and neighbouring countries including Bhutan, Bangladesh, Nepal, Sri Lanka and Myanmar. In a comprehensive account of cicada from this region, Price et al (2016) compiled and provided an annotated catalogue of cicadas of the Indian region, consisting of India, Bhutan, Bangladesh, Nepal, Sri Lanka including Myanmar; based on literature and type specimens in the collection of the British and other museums they have listed a total of 281 species of cicadas, with 189 species from India and Bangladesh, 19 species from Bhutan, 81 species from Myanmar, 46 species from Nepal and 22 species from Sri Lanka. An earlier detailed analysis of cicadas from Nepal by Sanborn (2015) had listed 59 species and Bhutan with 18 species and the Himalayan state of Sikkim in India lists 43 species.…”
mentioning
confidence: 99%